PERBANDINGAN PENGGUNAAN SINGLE INJECTOR DAN DOUBLE INJECTOR TERHADAP TORSI DAN DAYA PADA SEPEDA MOTOR EFI DENGAN KAPASITAS MESIN 110 CC MENGGUNAKAN BAHAN BAKAR PERTAMAX : Comparison of Using Single and Double Injector to Torque and Power on EFI Motorcycle with 110 cc Engine Capacity using Pertamax Fuel - Darwin Rio Budi Syaka; Sopiyan; Alfian Dwi Prayogo (Jurnal Konversi Energi dan Manufaktur, 2023)
Pertamax has the advantage of the pertatec compound protecting the engine from rust. In Pertamax fuel with an octane rating of 92 it works optimally and the rest of the combustion results. Meanwhile, an engine with a lower octane rating has the impact of burning fuel that explodes and has a risk of misalignment causing knocking symptoms. This research includes comparative research with experimental methods. The test results for a single injector (12 holes) have increased compared to a double injector (12 holes). 10.86 and on the double injector (12 holes) which is 12.25 so that the acceleration on the single injector is better than the double injector, the single injector (12 holes) which is 30.15 Kph/s and the double injector (12 holes) which is 29.37 Kph/s, resulting in greater torque and power values, namely single injector (12 holes) of 9.71 Nm and power of 10.19 HP and double injectors (12 holes) of 9.7 Nm and power of 8. 97 HP with the greatest speed obtained single injector (12 holes) 103.91 Km/h and Double injectors (12 holes) 103.68 Km/h. So that a single injector with 12 holes is better used on 110 cc vehicles seen from the aspect of the Dynotest.